Potassium Efficiency of Wheat and Sugar Beet Evaluated Under Field Conditions (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted to investigate the potassium (K)efficiency of wheat and sugar beet under field conditions and to identifythe varying mechanisms or factors behind their efficiency. Data wereobtained from a long term fertilizer experiment, on a K "fixing" sandyclay loam in Bavaria, southern Germany, in which K fertilization ratesvaried from 0 to 1000 kg K ha-1 year-1 with the last K application in 1986.In 2003, sugar beet and spring wheat were sown on March 13 th and April4 th , respectively. At 4 and 5 harvests for wheat and sugar beet,respectively, random samples of shoots, roots and soil of each speciesfrom the unfertilized (-K) and the highest fertilizer level of 1000 kg K ha-1(+K) treatments were analyzed. Sugar beet and wheat had similar Kefficiency producing 76 % and 80 % beet and grain yield on unfertilizedcompared with fertilized treatments, respectively. As compared to wheat,sugar beet had a higher internal K requirement, two times higher shootgrowth rate (GRs), 34% to 48 % of the wheat root length (RL), andconsequently a larger GR/RL, that is higher demand for K uptake on theroots. However, sugar beet showed an exceptionally high uptakeefficiency of the single roots or influx, which was 5 times higher inunfertilized treatments, as compared with wheat. Wheat K efficiency wasattributed to a higher utilization efficiency or lower internal requirement,slow growing shoots and a large root system. Further investigations arenecessary to study the mechanism by which sugar beet was able toachieve a higher influx than wheat.
Keywords: Sugar beet; wheat; nutrient efficiency; potassium